Posaconazole as single or adjunctive antifungal in mucormycosis of the maxilla: systematic review and meta-analysis - Pardiwala Arwa; Datarkar Abhay N.; Manekar Varsha; Daware Surendra (Journal of Oral Medicine and Oral Surgery, 2023)
Introduction: The aim of this systematic review was to analyse the benefits of utilizing posaconazole as a single drug therapy or in combination with other antifungals for the treatment of maxillary mucormycosis  as opposed to sole use of amphotericin B. Materials and methods: Databases (MEDLINE via PubMed, Cochrane, EBSCO-host, Scopus, Science Direct, Clinical Trial Registry- India (CTRI) and Google scholar), review articles were searched from 1997 to 2022, using various MeSH terms. Results: After application of the inclusion and exclusion criteria, four articles were finally selected. Three-month survival rate and duration of hospital stay were analysed as primary outcomes. There was no difference in survival among cases of maxillary mucormycosis treated with either drug alone. Death reported after treatment with combination treatment was less as compared to that with amphotericin B alone; however, there was non-significant difference in survival among cases treated with posaconazole in addition to amphotericin B or amphotericin B alone. Conclusion: Posaconazole can be used a single drug therapy for the treatment of maxillary mucormycosis due to its benefits outweighing its risks. The limitations of this study are the paucity of studies and Randomized Controlled Trials available in the literature in this field of study.